Ecofriendly Organosolv Process for Pulping of Tender Coconut Fibre - Jincy, P. J.; Ravindranath, Anita Das; Sarma, U. S. (International Coconut Community, 2015)
The huge biomass generated by vendors of tender coconut is the broken husks refuse dumped along roads and highways in Kerala. These dumps become breeding grounds for diseased causing germs and carrier mosquitoes causing threat to human life. In order to avoid pollution and find use of the rejected biomass of tender husks, a study was carried out on pulping of tender coconut husk fibre which could be used for papermaking. The optimum pulping condition, the quality of the pulp and its yield was evaluated using different variables like time and temperature. It was observed that the organosolv process could efficiently remove lignin from the tender coconut fibre yielding maximum cellulose. During the traditional pulping processes such as Kraft pulping to isolate the cellulose fibers for the production of paper, the hemicellulose and lignin fractions are degraded, limiting their valorization possibilities. Organosolv pulping has been advocated as the environmentally benign version of the kraft process. Unlike other pretreatment methods, organic solvents can easily be recycled and reused. The lignin dissolved by organosolv pulping is easily recovered by dilution and is unsulphonated and relatively unmodified. Products like handmade paper, egg cartons, handicraft items, garden articles like paper pots could be made from the organasolv pulp of tender coconut husk fibre.